Implementation of a Patient Questionnaire in Community Pharmacies to Improve Care for Patients Using Combined Antithrombotic Therapy: A Qualitative Study - Renate C. A. E. van Uden; Marit A. Bakker; Stephan G. L. Joosten; Karina Meijer; Patricia M. L. A. van den Bemt; Matthijs L. Becker; Marcia Vervloet (MDPI AG, 2023)
For several indications or combinations of indications the use of more than one antithrombotic agent is required. The duration of combined antithrombotic therapy depends on indication and patient characteristics. This study investigated the use of an antithrombotic questionnaire tool that had been developed for pharmacists to detect patients with possible incorrect combined antithrombotic therapy. The objective of this study was to identify potential barriers and facilitators that could influence the implementation of the developed antithrombotic questionnaire tool in daily community pharmacy practice. A qualitative study was conducted at 10 Dutch community pharmacies in which the antithrombotic questionnaire tool had been used with 82 patients. Semi-structured interviews were conducted with pharmacy staff who used the antithrombotic questionnaire tool. The interview questions to identify barriers and facilitators were based on the Consolidated Framework for Implementation Research. The interview data were analysed using a deductive thematic analysis. Ten staff members from nine different pharmacies were interviewed. Facilitators for implementation were that the questionnaire was easily adaptable and easy to use, as well as the relative short duration to administer the questionnaire. A possible barrier for using the questionnaire was a lower priority for using the questionnaire at moments when the workload was high. The pharmacists estimated that the questionnaire could be used for 70-80% of the patient population and they thought that it was a useful addition to regular medication surveillance. The antithrombotic questionnaire tool can be easily implemented in pharmacy practice. To implement the tool, the focus should be on integrating its use into daily activities. Pharmacists can use this tool in addition to regular medication surveillance to improve medication safety in patients who use combined antithrombotic therapy.